CAPACITY ANALYSIS OF DRAINAGE CHANNELS ON PUBLIC ROADS IN FRONT OF THE SIDOARJO CLASS 1A RELIGIOUS COURT OFFICE: A REVIEW OF MAINTENANCE COSTS - Ernitasari, Windya Yunesti; Witjaksana, Budi; Patriadi, Andi (Transpublika Publisher, 2024)
Flooding in front of the Sidoarjo Class 1A Religious Court Office road happens frequently during the rainy season. It disrupts traffic and damages the roads. Flooding is caused by the condition of the drainage channels, which are not performing efficiently due to sediment barriers such as garbage, and some channels appear to be damaged. The existing channels can no longer accommodate the water discharge caused by the rain, thus water overflows from the drainage channels, flooding the main road. These conditions show the importance of handling drainage problems. One of the ways that can be taken is to evaluate the capacity of existing drainage channels. In this study, the evaluation of drainage channel capacity was carried out using the Hydrological and Hydraulics Analysis method. The purpose of this study to assess the suitability of the magnitude of the 5-year return period flood discharge with the capacity of the existing drainage channel, and to find a solution if the drainage system can no longer accommodate the magnitude of the proposed flood discharge. The chosen alternative was alternative 2 drainage channel rehabilitation with increased channel dimensions. Based on the calculated results, a channel dimension plan with a width of 0.6 m and a height of 0.80 m was necessary. The cost required for drainage channel rehabilitation was 750,605,179.00 rupiahs.